"[W]hat Beauty in Oriental Art Means": Asian Arts, Soft Diplomacy, and New Zealand Cultural Nationalism—The Loan Exhibition of Oriental Art, Christchurch, 1935. Issue 1 (1st July 2019) - Beattie, James; Stevenson, Louise
Abstract : This article presents new historical research on Asian art—particularly Chinese art—in New Zealand through the examination of the content and reception of the Loan Exhibition of Oriental Art, which was held in Christchurch from May to June 1935. It situates the exhibition within the context of Depression-era New Zealand, examines the place of Chinese art, in particular, in the developing cultural nationalism of New Zealand of this period, and highlights the role of one local connoisseur in the making of the exhibition. Moreover, the article's focus on the southern hemisphere fills a gap in global histories of Chinese art exhibition in this period.